Four Laws for the Artificially Intelligent. - Domowitz, Ian. (Business Expert Press, 2021)
Four Laws for the Artificially Intelligent redefines possibilities and offers leverage to turn AI visions into reality. It is a story of transformation: of people, of companies, and of artificial intelligence itself. The Four Laws is unique in its combination of stories and science illustrating how a technology competing with human consciousness is introduced and assimilated within a company. A work of creative nonfiction stretched on a frame of research, it is an essential trail guide for navigating the Industry Version 4.0 jungle in a search of the fruits of innovation.